2010
DOI: 10.1055/s-0029-1240758
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Effects Despite Limited Cell Survival of Bone Marrow-Derived Mesenchymal Stem Cells under Ischemia

Abstract: Bone marrow-derived mesenchymal stem cells (MSCs) are multipotent and secrete angiogenic factors, which could help patients with occlusive arterial diseases. We hypothesize that MSCs, in comparison to fibroblasts, survive better under hypoxic conditions in vitro and in vivo. MSCs and fibroblasts from L2G mice expressing firefly luciferase and GFP were cultured in normoxic and hypoxic conditions for 24 hours. In vitro cell viability was tested by detecting apoptosis and necrosis. MSCs released higher amounts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 18 publications
0
50
0
Order By: Relevance
“…Some studies have shown that MSCs could also achieve the biological effects by secreting VEGF. VEGF secreted by MSCs has been used in gastric ulcer and oral ulcer healing (El-Menoufy et al 2010;Hayashi et al 2008), in murine ischemic limbs leading to an increase in vessel density (Hoffmann et al 2010), in inhibiting the apoptosis of lung cells (Zhen et al 2010), in facilitating neurological function (Deng et al 2010), enhancing the repair and regeneration of critical sized bone defects (Kanczler et al 2010) and improving cardiac function in failing rat hearts (Tao et al 2009). Therefore, the VEGF 165 gene is the best target gene in gene therapy for promoting angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that MSCs could also achieve the biological effects by secreting VEGF. VEGF secreted by MSCs has been used in gastric ulcer and oral ulcer healing (El-Menoufy et al 2010;Hayashi et al 2008), in murine ischemic limbs leading to an increase in vessel density (Hoffmann et al 2010), in inhibiting the apoptosis of lung cells (Zhen et al 2010), in facilitating neurological function (Deng et al 2010), enhancing the repair and regeneration of critical sized bone defects (Kanczler et al 2010) and improving cardiac function in failing rat hearts (Tao et al 2009). Therefore, the VEGF 165 gene is the best target gene in gene therapy for promoting angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation of serum starvation and hypoxia could increase the secret of vasoactive substances [30]. While, eNOS is an important enzyme modulating the NO, a vasodilatation factor, especially in ischemia tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, improvement is limited. Cell apoptosis during transplantation may be one of the reasons for the poor effectiveness of the treatment (Stolzing and Scutt, 2006;Hoffmann et al, 2010). Erythropoietin (EPO) is a glycoprotein that regulates the growth and differentiation of erythroid progenitor cells.…”
Section: Introductionmentioning
confidence: 99%